Pengaruh Field Trip Berbasis Scienctific Terhadap Kemampuan Berpikir Kreatif Siswa SMA - Ratna, Rena Dwi; Ratnasari, Jujun; Ramdhan, Billyardi (FKIP Universitas Muhammadiyah Sukabumi, 2019)
The purpose of this study is 1) To find out the creative thinking skills of students in the experimental class and conventional learning in the control class. 2) To compare the increase in each indicator of creative thinking using the scienctive-based Field Trip method. The research subjects were class X Science in Sukabumi Regency with 28 students. The research methodology used in this study is Quasi experiment with Non Equivalent Control Group Design, data collection techniques using purposive sampling. From the data analysis, it is known that the average value of the posttest of the experimental class students with a value of 77.88 using the Scientific-based Field Trip method and the average poststest value of the control class students by not using the Direct Intruction method is 66.76. There are significant differences in student learning outcomes, this is evidenced by the T-test obtained because Tcount = 4.444> TTabel = 2.004 then H0 is rejected and H1 is accepted, meaning that the scientific method of field trip learning has a significant effect on students' creative thinking abilities.